2003
DOI: 10.1002/app.13119
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electron beam irradiation on properties of fluorine‐containing poly(aryl ether ketone)s

Abstract: ABSTRACT:The influence of electron beam irradiation on the properties of fluorine-containing poly(aryl ether ketone)s (F-PEK), derived from 2,3,4,5,6-pentafluorobenzoic acid, was examined. Irradiation was performed with an electron beam at a dose of 3.63 ϫ 10 3 Gy s Ϫ1 for which the corresponding doses were 29.0, 51.0, and 94.5 MGy. Tensile strength at break increased up to a dose of 29.0 MGy and then decreased very slightly with irradiation. Elongation at break was more susceptible to irradiation and decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Kimura and coworkers [7] prepared fluorine containing poly(ether ketone)s (PEKs) from 2,3,4,5,6-pentafluoro benzoic acid and studied the influence of electron beam irradiation on the properties of poly(ether ketone)s. They reported that thermal stability and transparency of PEKs improved significantly after irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Kimura and coworkers [7] prepared fluorine containing poly(ether ketone)s (PEKs) from 2,3,4,5,6-pentafluoro benzoic acid and studied the influence of electron beam irradiation on the properties of poly(ether ketone)s. They reported that thermal stability and transparency of PEKs improved significantly after irradiation.…”
Section: Introductionmentioning
confidence: 99%